ANALISIS KANDUNGAN FORMALIN PADA BERBAGAI JENIS IKAN LAUT BASAH DI BEBERAPA PASAR IKAN DI KOTA PADANG - Beby Rahim; Elmatris Elmatris; Hendriati Hendriati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Background: Fish is a superior food because it contains good for health. The protein and water content makes the fish spoil quickly. Various efforts were made by traders to prevent spoilage, to prohibited methods such as giving formalin. This is prohibited in BPOM Regulation number 7 of 2018 because it can have an impact on health. Objective: This study aims to identify formalin content qualitatively and quantitatively in wet sea fish in several fish markets in Padang City. Methods: This study used a descriptive cross sectional method with a population of all wet sea fish in five fish markets in Padang City (Pasar Raya, Pasar Pantai Padang, Pasar Gaung, Pasar Pasir Jambak, and Pasar Tanah Kongsi). A total of 75 samples were divided into small, medium, and large fish which were taken by multi-stage and simple random sampling. The samples were tested at the West Sumatra Provincial Health Center Laboratory from February to August 2022. The samples were tested qualitatively by the spot test method using formalin main reagent (FMR). Positive samples were followed by quantitative examination using UV-Vis spectrophotometry. Results: The results showed that there were 31 positive samples containing formalin with the highest number of positives found at the Pantai Padang Market. The highest level of formalin was found in one of the 4 positive samples at Pasar Gaung, which reached 15,530 ppm.